If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -2) + -5x = 5 + -2x Reorder the terms: 2(-2 + 3x) + -5x = 5 + -2x (-2 * 2 + 3x * 2) + -5x = 5 + -2x (-4 + 6x) + -5x = 5 + -2x Combine like terms: 6x + -5x = 1x -4 + 1x = 5 + -2x Solving -4 + 1x = 5 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -4 + 1x + 2x = 5 + -2x + 2x Combine like terms: 1x + 2x = 3x -4 + 3x = 5 + -2x + 2x Combine like terms: -2x + 2x = 0 -4 + 3x = 5 + 0 -4 + 3x = 5 Add '4' to each side of the equation. -4 + 4 + 3x = 5 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 5 + 4 3x = 5 + 4 Combine like terms: 5 + 4 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| X-(45)=16 | | (-2x^4y^2)= | | 73-5x=40x+23 | | 0=x^5+4x^4+4x^3 | | (n-5)*8=16 | | N^2+5n-265=0 | | 2x+8=8x-5 | | 6x^2+7x+3=26 | | x-3y=19 | | 36/9*2+6 | | 3t-7=-2t+38 | | y^2+4y^1+2y^0=0 | | -6x-34=3x+11 | | 17g+3=11g+3g | | 13x^2=3x | | -7x-33=2x+12 | | y^2+3y^1+9y^0=0 | | (6x-12)/(3)=(4x+12)/(12) | | 4x^5-10x^2=0 | | 3.4c/(5c+1)=-12.2 | | 2a(b-2c)-3b(2a+3c)= | | 125-216c^3=0 | | -3(2t-2)+4t=3t-6 | | 186-7x=38x+16 | | 8x-5=6x-1 | | 4x^3-12x^2+4x+4=0 | | (x/(x^2-x-6))-(x/(x^2-7x+12)) | | n+23=40 | | 2x+(3)/(4)=3x-(3)/(4) | | 0.12(y-9)+0.16y=0.18y-0.01(60) | | 5/6(12-5b)=35 | | 3a(b+c)+2b(a+c)-c(2a+3b)= |